2015
DOI: 10.1016/j.icarus.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Realistic uncertainties on Hapke model parameters from photometric measurement

Abstract: The single particle phase function describes the manner in which an average element of a granular material diffuses the light in the angular space usually with two parameters: the asymmetry parameter b describing the width of the scattering lobe and the backscattering fraction c describing the main direction of the scattering lobe. Hapke proposed a convenient and widely used analytical model to describe the spectro-photometry of granular materials. Using a compilation of the published data, Hapke (2012, Icarus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 38 publications
0
44
0
Order By: Relevance
“…To quantify the evolution of the photometric behavior of each sample with the wavelength, we used the procedure developed by Fernando et al (2013Fernando et al ( , 2015 using the fast implementation strategy of Schmidt and Fernando (2015). This methodology uses a Bayesian approach to estimate photometric parameters from the Hapke model (Hapke, 1993).…”
Section: Inversion Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To quantify the evolution of the photometric behavior of each sample with the wavelength, we used the procedure developed by Fernando et al (2013Fernando et al ( , 2015 using the fast implementation strategy of Schmidt and Fernando (2015). This methodology uses a Bayesian approach to estimate photometric parameters from the Hapke model (Hapke, 1993).…”
Section: Inversion Methodsmentioning
confidence: 99%
“…The prior information about model parameters (no information is defined as uniform PDF) combined with prior information about observations (a Gaussian PDF) are fused to infer the solution by using Bayes theory. The final state of information (posterior PDF of each parameter) is numerically sampled, using a Monte Carlo Markov Chain (Mosegaard and Tarantola, 1995) with an adaptative Metropolis method (Schmidt and Fernando, 2015), to calculate the posterior PDF.…”
Section: Inversion Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20][21][22][23][24][25][26] The isotropic multiple scattering approximation (IMSA) is an approximate solution to an RTE based on the Chandresekhar-Ambartsumian method of invariance. 4 In the Hapke treatment of the RTE, five orders of scattering are considered, and the single scattering contribution through the single scattering phase function is treated in an exact form; however, for multiple scattering contributions, the phase function is assumed to be isotropic.…”
Section: Radiative Transfer Models For Retrieval Of Sediment Geophysimentioning
confidence: 99%
“…In the case of the Hapke model, the entangling of its parameters, mainly the w, g sca andθ , have been widely criticized for a few decades (Helfenstein and Veverka, 1989). Nevertheless Fernando et al (2013), Fernando et al (2015a) and Schmidt and Fernando (2015) have recently applied a Bayesian inversion to study the probabilistic density function of each Hapke parameter and their degeneracy. Their study has found that w, b, c andθ follow a unimodal distribution around the solution and the parameters can be described with a mean and standard deviation when uncertainties are lower than about 5%.…”
Section: H(x W)mentioning
confidence: 99%